Pedunculated liver hemangioma mimicking stomach neoplasm - Aydın, Sonay; Fatihoğlu, Erdem; Ergün, Elif; Koşar, Pınar Nercis (The European Research Journal, 2018)
Hepatic hemangiomas are the most frequently seen benign liver mass. However, exophytic hepatic hemangiomas, particularly pedunculated ones are very rare. They have various appearances that make the diagnosis difficult. We report a pedunculated hemangioma case which was misdiagnosed as gastrointestinal stromal tumor on computerized tomography scan. Magnetic resonance imaging revealed that the tumor was a hepatic hemangioma with a long peduncle originating from the right edge of the liver, extending into perigastric area. Hepatic hemangioma with a long peduncle can be mistaken with other abdominal masses. Remembering this entity and knowing its imaging characteristics are the keys to diagnosis.